Mineral chemistry and geochemistry of serpentinites from the Bianmagou ophiolite in the North Qilian Belt, NW China: Implications for protoliths, melt extractions, and melt/fluid metasomatism. (4th August 2021) - Zhao, Jing; Wang, Yujing; Gao, Yilin; Zhao, Bingshuang; Peng, Xiuhong; Li, Jie; Long, Xiaoping
Abstract : The North Qilian Belt in northwestern China contains a large number of ophiolites. Most ultramafic rocks from the ophiolites have been entirely transformed into serpentinites because of extensive serpentinization, making it difficult to determine their origin and tectonic significance and further hindering advancements in the understanding of the evolutionary history of the Palaeozoic North Qilian Ocean. In this study, we present new mineral chemistry and whole‐rock geochemistry analyses (including rare earth elements, [REE]) for the serpentinites from the Bianmagou ophiolite to discuss their protoliths, geodynamic environment, melt extractions, and melt/fluid interactions. The mineral chemistry of the relic minerals (e.g., olivine, orthopyroxene, and spinel) and the whole‐rock geochemical compositions (e.g., Mg #, Ni, etc.) strongly demonstrate that the protoliths of the serpentinites were refractory mantle residues after melt extractions and probably emplaced into a tectonic regime of mid‐ocean ridge akin to abyssal peridotites. They experienced high degrees of partial melting (15–20%) recorded by spinel Cr # values and bulk incompatible elements (e.g., Ti, heavy rare‐earth element), resulting from multiple episodes of melt depletion in the lithospheric mantle. Moreover, the serpentinites commonly have U‐shaped chondrite‐normalized REE patterns. The significantly elevated LREEs probably reflect the early partial‐melting processes overprinted by later melt‐dominated metasomatism. The medium to strong enrichment of certain fluid‐mobile elements (e.g., U, Pb, Ba, Sr, As, etc.) in the studied serpentinites was a consequence of the fluid/rock interactions during serpentinization. Overall, despite the variable serpentinization they experienced, this study indicates that the mineral chemical and geochemical proxies of serpentinites provide reliable constraints on the petrogenesis and mantle metasomatism of ancient ophiolites. Abstract : The Bianmagou serpentites are mantle residues of multi‐episode melt extractions. The protoliths of the serpentinites was generated in the mid‐ocean ridge of North Qilian Ocean. The protoliths of the serpentinites had experienced the significant melt/fluid metasoamtism.